A pintura mural decorativa no interior de casas da capital mineira: mestres artistas e os diversos modos de fazer - Tatiana Duarte Penna (2021)
This thesis addresses of decorative murals found inside private and public buildings in the city of Belo Horizonte, Brazil, from its foundation in 1896 up to 1940, when an eclectic style prevailed across the city’s architecture. Modern from its birth, the city still undergoes transformations to this day, with its buildings being demolished and/or replaced with constructions of varying tastes and trends, leading to a significant loss of decorative murals as an art form. Overlooked by heritage preservation policies, these murals have remained hidden and tucked away from the eyes of those who should ensure their preservation. The approach used to study these heritage assets involved salvaging their trajectory through the cities and their own history. We sought to identify the values they embody and give visibility to this art form by looking into the master artists who came to this city and by identifying the techniques used and the types of ornamentation applied to the walls on the inside and on the balconies and porches of the selected buildings. We established that their initial function was to evoke scenes from the homelands left behind in the pursuit of new, modern horizons, and to enhance the beauty and value of the buildings in accordance with the European taste, which had so far been the norm for public constructions. We noticed that not only the uses and functions, but also the values of decorative paintings shifted throughout history, influenced by the varying political and economic contexts and by heritage preservation policies. Hence, a narrative was constructed by combining architecture, restoration theory and value theory; with architecture being the foundation stone of decorative mural painting – providing shelter for and protecting this type of pictorial decoration – restoration theory being the framework that helps us understand how the values of heritage evolved from ancient to contemporary times, and value theory being the tool that enabled us to analyze and discuss past and present values. The choice of private buildings was based on the work I have carried out as a restorer of heritage assets. The analysis of heritage registers held by the Directorate of Cultural Heritage and Public Archive of Belo Horizonte, along with research into publications by several authors on the city’s decorative paintings, made it possible to track private buildings containing interior decorative murals. Public buildings served as a basis for comparison for private constructions as regards the artists, the types of ornamentation and the techniques used. We also suggest a few protocols for accessing and enjoying these heritage assets so they can be seen, valued and thereby incorporated into heritage preservation policies. Hidden between four walls, absent from architectural heritage registers, poorly documented or done so in a decentralized manner, decorative mural paintings – which are often not recognized as an art form – have been forgotten, abandoned and inevitably doomed to fade into nothingness. In light of this, the objective of this thesis to restore the decorative murals paintings to their place of memory and history of Belo Horizonte.